Analisis Harga, Inovasi, dan Kualitas Layanan Aplikasi Maxim Terhadap Keputusan Konsumen - Vitha Audya Putri; Nurbaiti Nurbaiti; Ayu Nursari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study was conducted with the aim of identifying and analyzing the influence of price, innovation, and service quality variables on consumer decisions in using the Maxim online transportation service. The background of this research is the increasing competition in the online transportation industry in Indonesia, which encourages companies to continuously improve their marketing strategies to attract and retain customers. As one of the rapidly growing online transportation service providers, Maxim needs to understand the factors that influence consumer decisions in order to compete effectively. The method used in this research is a quantitative approach, with data collected through questionnaires distributed to 134 respondents who are active users of Maxim's transportation services. The data collected were analyzed using multiple linear regression to examine the effect of each independent variable (price, innovation, and service quality) on the dependent variable (consumer decision). Validity and reliability tests were also conducted to ensure the research instrument was appropriate for use.The results of the study show that all three independent variables—price, innovation, and service quality—have a positive and significant effect on consumer decisions. This means that the more competitive the price offered, the higher the level of innovation provided, and the better the perceived service quality, the more likely consumers are to choose and continue using the Maxim online transportation service.These findings provide practical implications for Maxim’s management in designing more targeted marketing strategies and service improvements, as well as strengthening the company’s position in facing market competition.